‘The reason why I got it … ’ – messages from people diagnosed with leptospirosis about infection in the workplace and its impact on livelihoods - Prinsen G; Benschop J; Collins-Emerson J; Nisa S; Yeung P (Taylor and Francis Group on behalf of the Royal Society of New Zealand, 2024)
In Aotearoa New Zealand, leptospirosis is a disease that mostly affects people working with livestock on farms and in abattoirs, with Māori and Pasifika workers more likely to be hospitalised than others. This article shares an analysis of thirteen interviews with people diagnosed with leptospirosis. They were asked to advise colleagues and employers, as well as share how their illness had affected their income – informing health officials and workplace insurers. Their comments suggest that most workers are aware of the importance of Personal Protective Equipment (PPE) and safe operating environments, and they know how they contracted the disease. However, they remove PPE or take shortcuts knowingly, often under time pressure. Comments on the financial impact of their illness suggest most farmers received support from family and community, but most meat-processing workers did not. Worse, while most farmers said their financial losses were limited, many meat-processing workers felt forced to return to work too soon because they needed the income. Farmers were almost exclusively farm owners. Financial assistance (ACC) is more needed for some than for others. However, while such assistance is welcomed when it arrives, all interviewees described personal interactions with the administration of financial assistance as disrespectful or dispiriting.
Keywords: Zoonotic infection risk management; financial impact occupational leptospirosis; transdisciplinary research; semi-structured interviews